LncRNA HOTTIP modulated by Hedgehog signaling drives colorectal cancer progression by promoting HUWE1-mediated ubiquitin‒proteasome degradation of p53 - Hui Wang; Weiwei Jiao; Defu Li; Zhengping Yu; Huqiao Luo; Jie Zhang; Yuanbing Zhang; Hai Rao; Quqin Lu; Bing Zhao; Shiwen Luo (Cell Death and Disease)
Abstract The Hedgehog (Hh) pathway plays critical roles in regulating appropriate tissue morphogenesis and organ formation in the gastrointestinal tract, and its dysregulation has been closely linked to the malignant progression of colorectal cancer. However, the underlying mechanisms are poorly understood. Here, we report that the long noncoding RNA HOXA distal transcript antisense RNA (lncRNA HOTTIP) is a novel Hh target gene and a Hh pathway effector. Activation of Hh signaling induced the expression of the lncRNA HOTTIP. The overexpression of the lncRNA HOTTIP promoted colorectal cancer cell proliferation and tumor growth, whereas HOTTIP knockout exerted the opposite effects in vitro and in vivo. Compared with control mice, AOM/DSS-colorectal cancer model mice with lncRNA Hottip overexpression in Villin-Cre epithelial cells presented notable increases in tumor number and size. Moreover, lncRNA HOTTIP overexpression increased the proliferation and viability of organoids derived from colorectal cancer patients. Mechanistically, the lncRNA HOTTIP binds to HUWE1 and promotes its E3 ubiquitin ligase activity toward p53 and mediating HUWE1-dependent proteasomal turnover of p53, which decreases the level and activity of p53 and results in the overexpression of p53 pathway downstream target genes important for cell proliferation and survival. From a clinical perspective, high levels of the lncRNA HOTTIP were detected in colorectal cancer tissues and were strongly correlated with poor prognosis in colorectal cancer patients. Together, our findings demonstrate that the lncRNA HOTTIP, a novel effector of the Hh pathway, drives colorectal cancer progression by promoting HUWE1-dependent ubiquitin‒proteasome degradation of p53. These findings reveal critical roles of the Hh-HOTTIP-p53 signaling axis in colorectal cancer progression and suggest a potential therapeutic target for colorectal cancer.